Analisis kepuasan penggunaan website Perpustakaan UIN Sunan Kalijaga Yogyakarta dengan metode WebQual pada masa pandemi Covid-19 - Wisnu Ramadhon; Anis Masruri (FPPTI Jawa Tengah, 2022)
The purpose of this research is to analyze the satisfaction of using the library website at the UIN Sunan Kalijaga Yogyakarta Library with the websqual 4.0 method which consists of usability, information quality and service interaction quality. The sample used was 98 respondents who were users of the UIN Sunan Kalijaga Yogyakarta Library website. The data collection method in this study used a questionnaire with a Likert scale distributed using googledocs. The data analysis method uses Descriptive Statistical Analysis, while for hypothesis testing using Multiple Linear Regression with SPSS version 24. The results showed that the quality of usability could provide positive and significant user satisfaction to the use of the UIN Sunan Kalijaga Yogyakarta Online Library during the Covid-19 Pandemic with (sig t-count value (0.000) <Level of Significant (0.05)). the quality of information can provide positive and significant user satisfaction to the use of the Online Library of UIN Sunan Kalijaga Yogyakarta during the Pandemic Period with (sig t-count (0.034) <Level of Significant (0.05)) and the quality of interaction can provide positive user satisfaction and significant to the use of the Online Library of UIN Sunan Kalijaga Yogyakarta during the Pandemic Period with (sig t-count (0.019) <Level of Significant (0.05)).